Good morning, midnight. - Rhys, Jean. (London : Penguin Books Ltd, 2000)
Sasha has returned to Paris, the city of both her happiest and most desperate moments. Her past lies in wait for her in cafes and bars, blurring all distinctions between nightmare and reality. When she is picked up by a young man, she begins to feel that she is still capable of desires.
9781408299678 (set)
Keywords: Women